Comparative Studies on Acetylcholinesterase Characteristics between the Aphids, Sitobion avenae and Rhopalosiphum padi - Lu, Y. H. (University of Wisconsin Library, 2013)

(untitled)
The aphids Sitobion avenae (Fabricius) and Rhopalosiphum padi (Linnaeus) (Hemiptera: Aphidiae) are serious pests on grain crops and usually coexist on late period of wheat growth in China. Bioassays showed that R. padi was more susceptible than S. avenae to pirimicarb that is used for wheat aphid control, and the determination of acetylcholinesterase (AChE, EC 3.1.1.7) sensitivity showed that the sensitivity of AChE to pirimicarb was significantly higher in R. padi than in S. avenae (Lu and Gao 2009). AChE is the target enzyme of the carbamates, including pirimicarb, hence, to understand the mechanism responsible for the tolerance difference to carbamate insecticides of S. avenae and R. padi, we purified AChE from both aphid species using procainamide affinity column and characterized the AChE. The purification factor and yield from S. avenae (234.7-fold and 92.9%) were far higher than that from R. padi 17.3-fold and 13.9%. The results of substrate and inhibitor specificities of purified enzyme from both S. avenae and R. padi indicated that the purified enzyme was a typical AChE. The crude AChE extract from S. avenae was 5.4-, 4.3- and 8.1-fold less sensitive to inhibition by pirimicarb, methomyl and thiodicarb, respectively, than that from R. padi, whereas for the purified AChE, S. avenae was only 1.6-, 1.3- and 1.7-fold less sensitive to inhibition by pirimicarb, methomyl and thiodicarb, respectively, than R. padi. This suggests that eserine and BW284C51 may bind with other proteins, such as carboxylesterase, in the crude extract to reduce their inhibition against AChE. These results are useful for planning the chemical control of aphids on wheat.